Peran Manajemen Mutu dalam Meminimalisir Keterlambatan Pengiriman Barang pada Operasional Jasa Logistik - Chiara Zahra Maulani; Eky Setiawati; Raudhah Nur Azizah; Veryna Dewi Handayani (Universitas 45 Surabaya, 2024)
Quality management plays a crucial role in minimizing delivery delays in the logistics process. Factors such as input errors, fleet maintenance, and fleet shortages can contribute to delays. Companies need to focus on delivery services, provide training to employees, and utilize information technology to enhance efficiency and service quality. Total Quality Management (TQM) can serve as an effective strategy in improving service quality and customer satisfaction. Companies should also address fleet improvements, better input processes, and enhanced services to overcome delivery delays. The importance of quality management in reducing delivery delays in logistics service operations is highlighted, with factors such as delivery speed, delivery process efficiency, and limitations in manpower, machinery, work methods, raw materials, market, and finances contributing to delays. Quality management can aid in enhancing the quality of operational logistics services and customer satisfaction. The research methodology employed was a survey with data collection conducted through Google Forms.